Development of Baltic-Mediterranean geopolitical strategy as continuation of Stepan Rudnytskiy’s ideas - Serhii Sonko; Yuriy Kyselov (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2017)
An investigation of the up-to-date geopolitical and civilization factors viewing the geopolitical choose ofUkraineis the goal of our publication. It is marked that different issues connected with the euro-integrative geopolitical vector ofUkraineneed serious and multidiscipline scientific researches. The geopolitical state ofUkraineis characterized by its “bufferness” between East and West that calls a couple of problems connected with its boundary localization. Than, the challenges of our time caused by the newest expansion ofRussiaare not principally new phenomenon in the Ukrainian history. It is stressed that developing byUkrainethe Baltic-Mediterranean geopolitical doctrine founded almost one hundred years ago by the Academician Stepan Rudnytsky is the best strategy for our country caused by the non-principal policy toUkraineof the leading West-European states. An oriental list of countries that can be joined to the Baltic-Mediterranean axis is lined. Some immediate actions that the state must realize for renewing the control over natural resources of the country by the Ukrainian people – by the authors’ thought – are: renewing landscapes of Velyky Luh throw the liquidation of Kakhovka water-reservoir, blockade the North-Crimean channel on the administrative boundary between the Kherson region and Crimea and also active involvement of the foreign investitions into the sea-portal and transport infrastructure of the Black-sea regions of Ukraine.